Reflexões hermenêutico-fenomenológicas sobre a condição paterna - Yamaguti, Alexandre Collarile (2015)
The following work aimed to reconstruct the ontological bases for the compreheension of fatherhood through the hermeneutical-phenomenological method, as proposed by Martin Heidegger. This paper consists of an introduction and three chapters. The first chapter is concerned about mapping the academic articles on contemporary fatherhood. The literature review tells us that fathers live in a transition moment where in the same time they search for another way of relationships with their children, there is a lack of solid models and social conditions for the transitions of these experiences, pointing to the necessity of interventions on the sphere of public policies, supportive spaces to a conscious fatherhood and fortification of the bound between father and baby, as well of the deepening of researches about the theme of fatherhood. In general, the researches about the topic investigate the phenomenom of fatherhood from a position that still possesses normative and natural roots, without giving the necessary attention for a radical reconstruction of the ontological conditions that possibilitates those interpretations. This way, the second chapter introduces the thought of Martin Heidegger as an unity that must be considered from the history of the forgetting of being. Being the phenomenology a philosophical stream that emerges on the moment of the end of traditional philosofy and the crisis of modern science, it s a thought that brings the possibility of clarification of the ontological bases that possibilitates the unveiling of the phenomena. Important notions both from Being and Time (1927), and the later papers post the 1930 years, are presented as a form of contextualizing the heideggerian thought. Finally, the third chapter occupies of an effective reconstruction of the interpretative basis of fatherhood, showing that the difficulties experienced from the contemporary father are not, in a more originary scope, results of their lack of models, but before, from the unbrilded spirit of his epoch, which provides a deep existencial rootlessness